The Influence of Work Environment, Pay Satisfaction, and Job Stress on Employee Performance A Literature Review - Daniel Dewantoro Rumani; Untung Lestari Nur Wibowo; Arief Rusdyansyah; Cris Kuntadi (DINASTI RESEARCH, 2023)
Employee performance plays an important role in determining the sustainability and success of the company. Some of the factors that affect employee performance include the work environment, salary satisfaction, and work stress levels. In this paper, we will review the results of studies that examine the influence of each of these factors on employee performance. Studies show that a good work environment has a positive influence on employee performance, while salary satisfaction levels and work stress levels have varying influences depending on their levels. From this analysis, it can be concluded that the company must pay attention to such factors to ensure optimal employee performance.